Delivering health and social services. (20th October 2021) - Webb, E; Karanikolos, M
Abstract: Dual delivery of COVID-19 and non-COVID-19 services proved to be the core challenge of the service delivery response. Health systems responded by implementing strategies to manage a surge in demand for both health and social services, while continuing to provide other necessary health care services. These involved adapting or transforming patient care approaches, including the coordination of care across levels (e.g., acute vs. outpatient) and settings (e.g., PHC vs. long-term care), and coordinating response measures with social services provided outside of health system. The initial capacities and available reserves of physical infrastructure, such as hospital and intensive care unit (ICU) beds, the organization and coordination of service delivery and previous experience of responding to epidemics such as SARS or MERS or other health system shocks, influences a country's ability to anticipate and cope with surges in demand for health and social services. This presentation will provide an overview of strategies on ensuring the ability to cope with surge in demand for and managing provision of services for COVID and non-COVID patients, including social services. It will also cover strategies on increasing capacity to cope with surges of need for physical resources, such as infrastructure, equipment and medical supplies. A brief overview of key metrics to assess resilience in delivery of health and social services will also be provided.